A Critical Examination of Scientism and its Implications - Arshad, Muhammad Rasheed (Annals of Human and Social Sciences, 2024)
The idea of scientism and the problems that surround it are examined critically in this study. Scientism, the belief that the scientific method and its findings are the only reliable path to knowledge, has received a lot of attention in contemporary debate. Even if science unquestionably offers insightful knowledge about the natural world, accepting scientism at face value has detrimental implications on epistemology, ethics, and society as a whole. To analyse and assess scientism, a qualitative research design was used. Relevant documents, academic works, and philosophical literature were examined to provide context-rich understanding. The results of the investigation showed that scientism undermines marginalises alternate forms of knowledge, demolish traditional ethics and humanistic values. These results demonstrate the drawbacks and negative effects of scientism. It is crucial to adopt a more inclusive and balanced approach to epistemology, ethics and ontology embracing insights from philosophy, religion, and the humanities alongside scientific contributions.